Performing collaborative research: a dramaturgical reflection on an institutional knowledge brokering service in the North East of England - Peter van der Graaf; Janet Shucksmith; Rosemary Rushmer; Avril Rhodes; Mark Welford (BMC, 2019)
Abstract Background To increase the uptake of research evidence in practice, responsive research services have been developed within universities that broker access to academic expertise for practitioners and decision-makers. However, there has been little examination of the process of knowledge brokering within these services. This paper reflects on this process within the AskFuse service, which was launched in June 2013 by Fuse, the Centre for Translational Research in Public Health, in North East England. The paper outlines the challenges and opportunities faced by both academics and health practitioners collaborating through the service. Methods The authors reflected on conversations between the AskFuse Research Manager and policy and practice partners accessing the service between June 2013 and March 2017. Summary notes of these conversations, including emails and documents relating to over 240 enquiries, have been analysed using an auto-ethnographic approach. Findings We identified five challenges to knowledge brokering in an institutional service, namely length of brokerage time required, limits to collaboration, lack of resources, brokering research in a changing system, and multiple types of knowledge. Conclusions To understand and overcome some of the identified challenges, we employ Goffman's dramaturgical perspective and argue for making better use of the distinction between front and back stages in the knowledge brokering process. We emphasise the importance of back stages for defusing destructive information that could discredit collaborative performances.